2021
DOI: 10.3390/ani11082476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation with Lipids of Different Unsaturation Degree on Feed Efficiency and Milk Fatty Acid Profile in Dairy Sheep

Abstract: Lipids of different unsaturation degree were added to dairy ewe diet to test the hypothesis that unsaturated oils would modulate milk fatty acid (FA) profile without impairing or even improving feed efficiency. To this aim, we examined milk FA profile and efficiency metrics (feed conversion ratio (FCR), energy conversion ratio (ECR), residual feed intake (RFI), and residual energy intake (REI)) in 40 lactating ewes fed a diet with no lipid supplementation (Control) or supplemented with 3 fats rich in saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
(93 reference statements)
2
2
0
Order By: Relevance
“…In this study, it was observed that the levels of oil used did not affect the productive parameters in the sheep and their offspring, which was similar to other studies carried out on sheep in which different oils were used in the diets; in some cases, over 6% of the DM was offered [11,[33][34][35]. However, there are reports in sheep and goats in which levels greater than 6% of the DM of oil were added to the diet without generating changes in productive behavior [36,37], as observed in dairy sheep of the Spanish Assaf breed that had 6% soybean oil added to their diets; this was similar to what happened in this trial for hair sheep in a tropical region.…”
Section: Productive Behavior Of Sheep and Lambssupporting
confidence: 83%
“…In this study, it was observed that the levels of oil used did not affect the productive parameters in the sheep and their offspring, which was similar to other studies carried out on sheep in which different oils were used in the diets; in some cases, over 6% of the DM was offered [11,[33][34][35]. However, there are reports in sheep and goats in which levels greater than 6% of the DM of oil were added to the diet without generating changes in productive behavior [36,37], as observed in dairy sheep of the Spanish Assaf breed that had 6% soybean oil added to their diets; this was similar to what happened in this trial for hair sheep in a tropical region.…”
Section: Productive Behavior Of Sheep and Lambssupporting
confidence: 83%
“…*signi cant differences in each column using chi-square analysisDiscussionSheep were fed fat sources to enhance the energy density of their diet. Many aspects of sheep production, especially reproductive performance, are affected by dietary fat supplementation(Hervás et al, 2021;Mirzaei-Alamouti et al, 2018). Total dry matter intake in this study met the recommendation of the NRC (NRC, 2007) which 970 g/head/day for pregnant ewes weighing ±20 kg.…”
supporting
confidence: 59%
“…From this point on, the central theme of this work is to determine the change in milk's fatty acid profile due to the dietary content of different PUFA levels during the lactation stage [19]. However, studies in sheep [27][28][29] and cows [30] when fed diets high in LA showed no adverse changes in rumen microbial activity, milk yield, and milk composition.…”
Section: Discussionmentioning
confidence: 99%